PENERAPAN PASAL 28 AYAT (1) UNDANG-UNDANG ITE DALAM PERSPEKTIF KEPUTUSAN BERSAMA MENTERI KOMUNIKASI DAN INFORMATIKA, JAKSA AGUNG REPUBLIK INDONESIA DAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA - NI LUH ARININGSIH SARI (Universitas Mahasaraswati K. Mataram, 2023)
Whereas several articles that regulate acts that are punishable by criminal acts in Law no. 11 of 2008 concerning Information and Electronic Transactions as amended by Law No. 19 of 2016 concerning Amendments to Law no. 11 of 2008 concerning Information and Electronic Transactions, in its implementation it still causes multiple interpretations and controversy in the community so that it is necessary to develop implementation guidelines for Law Enforcement Officials in carrying out their duties and authorities. How is the application of Article 28 paragraph (1) -Law no. 11 of 2008 as Amended by Law No. 19 of 2016 concerning Information and Electronic Transactions? One of the articles in its application must be guided by the Joint Decree of the Minister of Communication and Information, the Attorney General of the Republic of Indonesia and the Head of the State Police of the Republic of Indonesia No. 229 of 2021, Number 154 of 2021, Number KB/2/VI/2021 concerning Guidelines for the Implementation of Article Certain in Law no. 11 of 2008 as Amended by Law No. 19 of 2016 concerning Information and Electronic Transactions, namely Article 28 paragraph (1).